Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
8 Answers
- BattleaxeLv 710 years agoFavorite Answer
3x^2 - 15x = 42
3x^2 - 15x - 42 = 0
using quadratic equation:
x = (15 +/- SQR(225 - 4(3)(-42)))/2(3)
x = (15 +/- 27)/6
x = -2, 7
- .--
- DambarudharLv 710 years ago
3x^2 - 15x = 42 ==> x^2 - 5x = 14 (dividing throughout by 3)
==> x^2 - 5x - 14 = 0 == x^2 + 2x -7x -14 = 0 ==> x(x+2) - 7(x+2) ==> (x+2)(x-7) = 0
==> either x+2 = 0 or x-7 = 0 ==> x= -2 or x=7
- 10 years ago
3x^2 -15x = 42
3x^2 - 15x - 42 = 0
(x - 7) (3x+6) = 0
x - 7 = 0 3x + 6 = 0
3x = - 6
x = 7 x = - 2
Source(s): my brain - ?Lv 510 years ago
First you move 42 to the other side then you get 3x^2 -15x-42 then you factor with 6and7 so it would be(3x+6)(x-7)
3x^2-21x+6x-42 foil
- How do you think about the answers? You can sign in to vote the answer.
- Anonymous10 years ago
3x^2-15x=42
/3=
x^2-5x=14
x^2-5x-14=0
factorise- (x+2)(x-7)
x=-2 or x=7
hope you can see the process the get the answer.
- ranjankarLv 710 years ago
3x^2 -15x -42 = 0
x^2 -5x -14 = 0
x^2 + 2x - 7x -14 = 0
x ( x+2) -7( x+ 2) = 0
( x-7) ( x+2) = 0
x = 7 OR -2 ANSWER
- 10 years ago
3x^2-15x-42=0
x=(15+sqrt((-15)^2-4(3)(-42)))/2(3)=7
x=(15-sqrt((-15)^2-4(3)(-42)))/2(3)=-2